Customer Satisfaction on Product Quality and Services PT. Krida Dinamik Autonusa Bima - Hartoyo Hartoyo; Agussalim Agussalim; Dicki Hartanto (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2023)
This study aims to analyze the level of consumer satisfaction with the quality and service of companies in marketing goods. This research is a quantitative descriptive research, meaning that the researcher explains the causal aspects of consumer satisfaction with product quality and service in motorcycle sales in Bima. Respondents to this study were motorbike consumers from January to May 2023 at PT. Bima Autonusa Dinamik Krida as many as 63 people. The research instrument is a tool in the effort to collect research data. The instruments used in this study were questionnaires and sales and consumer documentation data, then the data were analyzed using quantitative descriptive analysis. The results of the study show that the level of consumer satisfaction is high, meaning that consumers have their own satisfaction with the quality or quality of the product and the form of the company's service. Therefore, for competitive companies to focus more on service and pay attention to quality or product quality.